Effect of Replacement of Conventional Feeds by Prosopis juliflora Pods and Citrullus lanatus Seed Cake on Haemato-Biochemical Parameters in Marwari Goats - Chharang, Dharmendra; Sharma, Tribhuwan; Karnani, Monika; ., Manju; Kumar, Rajesh (Indian Journal of Animal Nutrition, 2020)
An experiment was conducted to observe the effect of incorporation of mesquite (Prosopis juliflora) pods and watermelon (Citrullus lanatus) seed cake in complete feed with sixteen male Marwari goat kids of uniform conformation and age, divided into four groups. Four complete feed designated as T1, T2, T3 and T4 were formulated. T1 served as control having all the conventional ingredients; whereas, barley of control was replaced by mesquite pods in T2, cotton seed cake was replaced by watermelon seed cake in T3 and both barley and cotton seed cake were replaced by mesquite pods and watermelon seed cake in T4, respectively. All the four complete feeds were iso-nitrogenous and nearly iso-caloric. Haemato-biochemical parameters viz. haemoglobin, PCV, total serum protein and blood glucose, were worked out at fortnightly interval for 105 days of all individual animals. All parameters were found well within the normal range, i.e. 8.38, 8.26, 8.09 and 8.11 for haemoglobin (%), 27.87, 27.59, 27.78 and 27.87 for PCV (%), 72.03, 72.63, 69.66 and 71.66 for blood glucose (mg/dl), 7.26, 7.29, 7.17 and 7.33 for serum protein (g/dl) in T1, T2, T3 and T4 groups, respectively. It was concluded that dietary treatments had no adverse effect, but highly significant effect of period on haemato-biochemical parameters were observed in Marwari goat kids. Thus, barley and cottonseed cake could be safely and effectively replaced by mesquite pods and watermelon seed cake alone or in combination in the complete feed of goats.